2015
DOI: 10.1186/s12896-015-0185-1
|View full text |Cite|
|
Sign up to set email alerts
|

Cold shock induction of recombinant Arctic environmental genes

Abstract: BackgroundHeterologous expression of psychrophilic enzymes in E. coli is particularly challenging due to their intrinsic instability. The low stability is regarded as a consequence of adaptation that allow them to function at low temperatures. Recombinant production presents a significant barrier to their exploitation for commercial applications in industry.MethodsAs part of an enzyme discovery project we have investigated the utility of a cold-shock inducible promoter for low-temperature expression of five di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…This has recently allowed us to perform preliminary characterization of the selected enzymes. For example, activity assays on the His-SUMO fused chitinase described in our paper 1 suggests that the enzyme is truly psychrophilic with an optimal temperature around 20°C ( Fig. 1 ).…”
mentioning
confidence: 77%
See 4 more Smart Citations
“…This has recently allowed us to perform preliminary characterization of the selected enzymes. For example, activity assays on the His-SUMO fused chitinase described in our paper 1 suggests that the enzyme is truly psychrophilic with an optimal temperature around 20°C ( Fig. 1 ).…”
mentioning
confidence: 77%
“…By expressing the putatively psychrophilic genes in this E. coli system, we found that expression levels were generally high, and comparable to the commonly used T7 system which functions optimally at 37°C. 1 In contrast to the T7 system some soluble proteins were detected, however in most cases the yield was still too low for further experimentation. We therefore optimized cspA -driven expression by fusing the maltose-binding protein (MBP), thioredoxin (TRX), the small ubiquitin-like modifier (SUMO) and trigger factor (TF) N-terminally to these enzymes, in an attempt to improve solubility.…”
mentioning
confidence: 89%
See 3 more Smart Citations